An Introduction to Ancient Indian Political and Social Thought (c. 1500 BCE–550 CE) - Edward O'Mahony (Education About Asia, 2026)
While the Indian subcontinent is famous for its religious traditions, its equally rich tradition of political and social thought is not as well known. In recent decades, scholars in India and other countries have revived the study of the subcontinent’s ancient political and social philosophers. They have shown how the work of philosophers such as Kautilya and Kamendaka were closely intertwined with contemporary religious and cultural institutions and played an important role in both molding and supporting those institutions. The primary objective of these political philosophers was to maintain the Indian caste system and social order by making monarchical rule more effective. Kautilya is best known for developing a realpolitik approach to both domestic and foreign affairs. While he encouraged rulers to be ruthless in dealing with foreign and domestic opponents, Kautilya also encouraged monarchs to adopt a system of domestic paternalism, in which public works and other systems were used to benefit and placate ordinary people. He has been associated by some scholars with Chanakya, the main adviser to Chandragupta Maurya, the founder of the Mauryan Empire. The Laws of Manu similarly focused on maintaining the social order by assigning specific duties and obligations to each member of the caste system, including the king. Kamendaka, who may have lived during the late stages of the Gupta Empire, focused heavily in his work on the use of diplomacy and defensive military tactics to ensure the integrity of the state. This article is intended for middle school and high school World History teachers. Students in such classes generally learn a lot about India’s religious traditions, but relatively little about its political develop or ideas. Shorter versions of the article and worksheets are provided for use in the classroom.
Keywords: India; Politics; Social Thought; Kautilya; Religion; Philsophy; Caste